Pengaruh Lingkungan Kerja Terhadap Produktivitas Kerja Karyawan - Maludin Panjaitan (Sekolah Tinggi Ilmu Ekonomi-LMII Medan, 2018)
The purpose of the research is to investigate the effect of work environment and job productivity. The research was conducted among 50 employees in Medan, where all the employees became the respondents. The research employed a quantitative method and collected the data by using a questionnaire, which has been filled out by 50 respondents. The findings show that the work environment significantly affects the job satisfaction. Theoretical and practical implications are explained at the end of the paper.